The Benefits and Drawbacks of Sustainable Tourism in Siargao Islands, Philippines: An Exploratory Inquiry - Musico, Stephinejane; Pelmin, Monsour (Journal of Interdisciplinary Perspectives, 2025)
Siargao Islands, Philippines, is globally renowned for its world-class surfing spots, powdery white beaches, and vibrant local culture, positioning it as one of the world's leading island destinations. However, sustainable tourism remains a critical area of inquiry given the limited research on how local stakeholders manage the balance between tourism and conservation. This study addresses this gap by exploring the diverse local perspectives and providing context-specific insights into how the island can balance tourism growth with sustainability. An exploratory qualitative case study methodology was employed, utilizing thematic analysis of semi-structured, in-depth interviews with 19 purposively selected stakeholders including four municipal tourism officers, three accommodation providers, two tour operators, two tour guides, four food and beverage providers, one transportation provider, one local business owner, one startup entrepreneur, and one tourism educator. The findings reveal economic benefits of tourism, such as increased economic growth and livelihood opportunities, environmental conservation, and social and cultural enhancement. Drawbacks include resource strain, erosion of local culture, displacement, rising costs of commodities, and tourism-driven price increases. Reserving natural assets, economic and social development, and competitive advantage driven by tourism are essential for maintaining Siargao as a leading island destination. Nevertheless, fundamental sustainable tourism imperatives such as environmental stewardship, economic equity, and social balance must be prioritized to ensure the attainment of long-term development objectives, including robust infrastructure, financial sustainability, and social and ecological resilience. This study concludes that tourism is essential for building a resilient, balanced, and future-ready island economy. Furthermore, it advocates for the establishment of a unified regulatory framework, community-driven waste management systems, the support of local MSMEs and startups, the preservation of cultural heritage, investment in sustainable infrastructure, the promotion of complementary sectors, enhancement of participatory governance, and land-use protections to protect residents from the drawbacks of tourism.